The effect of pH on horseradish peroxidase-catalyzed oxidation of melatonin: Production of N1-acetyl-N2-formyl-5- methoxykynuramine versus radical-mediated degradation - Ximenes, Valdecir Farias [UNESP]; Fernandes, João Roberto [UNESP]; Bueno, Vânia B.; Catalani, Luiz H.; Oliveira, Georgino H. de [UNESP]; Machado, Rosângela G. P. [UNESP] (Wiley, 2007)
There is a growing body of evidence that melatonin and its oxidation product, N1-acetyl-N2-formyl-5-methoxykynuramine (AFMK), have anti-inflammatory properties. From a nutritional point of view, the discovery of melatonin in plant tissues emphasizes the importance of its relationship with plant peroxidases. Here we found that the pH of the reaction mixture has a profound influence in the reaction rate and products distribution when melatonin is oxidized by the plant enzyme horseradish peroxidase. At pH 5.5, 1 mm of melatonin was almost completely oxidized within 2 min, whereas only about 3% was consumed at pH 7.4. However, the relative yield of AFMK was higher in physiological pH. Radical-mediated oxidation products, including 2-hydroxymelatonin, a dimer of 2-hydroxymelatonin and O-demethylated dimer of melatonin account for the fast consumption of melatonin at pH 5.5. The higher production of AFMK at pH 7.4 was explained by the involvement of compound III of peroxidases as evidenced by spectral studies. On the other hand, the fast oxidative degradation at pH 5.5 was explained by the classic peroxidase cycle. © 2007 The Authors.
Keywords: 2-hydroxymelatonin; Horseradish peroxidase; Melatonin; Melatonin dimer; N 1-acetyl-N2-formyl-5-methoxykynuramine; horseradish peroxidase; melatonin; melatonin derivative; n1 acetyl n2 formyl 5 methoxykynuramine; unclassified drug; catalysis; catalyst; chemical reaction; demethylation; enzyme activity; enzyme metabolism; methylation; nonhuman; oxidation; pH; Horseradish Peroxidase; Hydrogen-Ion Concentration; Kynuramine; Oxidation-Reduction